2015
DOI: 10.1128/jvi.00064-15
|View full text |Cite
|
Sign up to set email alerts
|

A Metagenomics and Case-Control Study To Identify Viruses Associated with Bovine Respiratory Disease

Abstract: Bovine respiratory disease (BRD) is a common health problem for both dairy and beef cattle, resulting in significant economic loses. In order to identify viruses associated with BRD, we used a metagenomics approach to enrich and sequence viral nucleic acids in the nasal swabs of 50 young dairy cattle with symptoms of BRD. Following deep sequencing, de novo assembly, and translated protein sequence similarity searches, numerous known and previously uncharacterized viruses were identified. Bovine adenovirus 3, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
252
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(271 citation statements)
references
References 73 publications
12
252
3
4
Order By: Relevance
“…It is well known that BRD is a multifactorial respiratory infection marked by primary viral pathogens followed by bacterial colonization in the upper and lower respiratory tract. Similarly, a recent metagenomic study showed that bovine adenovirus 3, bovine rhinitis A virus, and IDV were the top three viruses associated with BRD, either alone or in coinfections, in dairy calves in California, which would be consistent with a hypothesis of IDV predisposing to or exacerbating disease (5). Of course, it is also likely that other conditions, such as inclement weather, transportation, and close housing, might contribute to the more severe IDV-induced disease in the field.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is well known that BRD is a multifactorial respiratory infection marked by primary viral pathogens followed by bacterial colonization in the upper and lower respiratory tract. Similarly, a recent metagenomic study showed that bovine adenovirus 3, bovine rhinitis A virus, and IDV were the top three viruses associated with BRD, either alone or in coinfections, in dairy calves in California, which would be consistent with a hypothesis of IDV predisposing to or exacerbating disease (5). Of course, it is also likely that other conditions, such as inclement weather, transportation, and close housing, might contribute to the more severe IDV-induced disease in the field.…”
Section: Discussionmentioning
confidence: 56%
“…A metagenomic study in dairy calves with bovine respiratory diseases (BRD) found that IDV was present in 62% of 50 calves that were coinfected with bovine adenovirus 3, bovine rhinitis A virus, or another BRD-associated pathogen (5). Our virologic surveillance found that IDV was present in 23.6% of 55 calves affected with BRD but in only 2.4% of 82 healthy calves upon arrival at the same facility (4).…”
mentioning
confidence: 80%
“…In the absence of a definitive diagnosis for the skin lesions, metagenomic sequencing was performed on seven lip lesions and one nonlesioned lip, according to previously described protocols, to further investigate a potential underlying viral etiology (21)(22)(23)(24). In brief, a tissue homogenate was centrifuged through a 0.22-m filter to enrich viral particles by size and then treated with nucleases to deplete host nucleic acids.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acids from nuclease-resistant viral particles were extracted using the QIAquick viral-RNA column purification system, followed by sequence-independent amplification using random priming. First-strand synthesis (for both DNA and RNA) was performed with a 28-base oligonucleotide whose 3= end consisted of eight random nucleotides (primer N1_8N, CCTTGAAGGCGGACTGTGAGNNNNNNNN), using Superscript III reverse transcriptase (Invitrogen) (21)(22)(23)(24). A second strand was synthesized using Klenow fragment DNA polymerase (New England BioLabs).…”
Section: Methodsmentioning
confidence: 99%
“…Z puli przebadanych próbek jedynie 6 surowic (2,8%) reagowało w teście HI, w niskim mianie (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), ze szczepami ludzkimi ICV.…”
Section: Zakażenia Ludzi Idvunclassified